ZOLTÁN GÁRDONYI’S CHAMBER MUSIC: A FANTASIA FOR VIOLIN AND ORGAN INSPIRED BY THE TUNE OF THE HYMN ENTITLED „AZ ÉN IDŐM, MINT A SZÉP NYÁR” (“MY TIME IS LIKE THE SHINY SUMMER”) - Gabriela COCA (Studia Universitatis Babeş-Bolyai. Musica, 2017)
This paper analyses Gárdonyi Zoltán’s musical work Fantasia for Violin and Organ inspired by the Tune of the Hymn entitled “Az én időm mint a szép nyár” (My Time is like the Shiny Summer). The musical work is placed in the historical context of its creation. Starting from the analysis of the basic song, the paper presents the architectural scheme of the piece, the proportions of the component sections, their metre and tonality. Then, it describes the musical content of each section, by illustrating the description of its content by musical examples.